Priorities for rapid and cost-effective vaccines to improve outbreak responses. - Sarah C Gilbert (PLoS Biology)
The use of vaccine platform technologies greatly reduces the time and money required to develop a novel vaccine against an infectious disease, but much work is still needed if vaccines are to protect the world from the next pandemic.